The effect of extended contact with community‐dwelling older adults on the ageist and helping attitudes of home care students: A single‐blind randomised controlled trial - Pekçetin, Serkan; Hasgül, Ergün; Yıldırım Düğeroğlu, Rasime; Arabacı, Zeynep (Wiley, 2021)
AbstractBackgroundAgeist and helping attitudes among undergraduate homecare students are a concern for educators, healthcare professionals and home care workers due to their potential to increase the marginalisation of older people and negatively impact quality of care.ObjectivesThe current study evaluated the effect of extended contact with community‐dwelling older adults on the ageist and helping attitudes of home care students.MethodsFifty‐five students attending a public university in Turkey were randomly assigned to the intervention group (n = 27) or control group (n = 28). The intervention group received positive theoretical education and had extended contact with community‐dwelling older adults, while the control group only received positive theoretical education. Before and after the intervention, the students’ ageist attitudes were evaluated with Kogan's Attitudes towards Old People scale (KAOP) and helping attitudes were evaluated with the Helping Attitude Scale (HAS).ResultsThere were statistically significant differences between pre‐ and post‐test mean KAOP total, positive ageism and negative ageism subscale scores in the intervention group (p < 0.05) and in KAOP negative ageism score in the control group (p < 0.05). HAS scores showed no significant post‐intervention change in helping attitudes in either group.ConclusionExtended contact with community‐dwelling older adults had a favourable influence on undergraduate health students’ ageism attitudes. These results suggest that contact with older adults may be an effective strategy to reduce ageism but may not increase helping behaviours.Implications for practicePositive contact experiences with community‐dwelling older adults can be used to reduce ageism in home care students.
Keywords: Attitude of Health Personnel; Home Care Services; Ageism; Attitude; Surveys and Questionnaires; Humans; Single-Blind Method; Independent Living; Students; Aged; 4. Education; 3. Good health; 10. No inequality